The need for a system design methodology to address challenges in wireless access in vehicular ad hoc networks - Chrysostomou, Chrysostomos; Lambrinos, Lambros; Djouvas, Constantinos (My University, 2010)
Vehicular networking is nowadays considered as one of the most important enabling technologies as it allows vehicles to communicate with each other (vehicle-to-vehicle (V2V) communication) and/or with roadside infrastructure (vehicle-to-infrastructure (V2I) communication). Vehicular ad hoc networks (VANETs) are ideal candidates for supporting various types of traffic applications, such as traffic safety, traffic efficiency and management applications, and infotainment type of applications. As a result, there is ongoing research concerning the efficient medium access control and multichannel coordination, separately. In this paper, we review a number of schemes proposed and stimulate the discussion on the need for a generic system design methodology to address efficiently the challenges in the wireless access in vehicular ad hoc networks. Specifically, the aim shall be to design an efficient and robust system architecture that deals with the wireless medium access and multichannel coordination in all possible environments (V2V and V2I in urban, suburban, and highway) and allows differently prioritized types of traffic applications to coexist.
Keywords: Vehicular ad hoc networks (Computer networks); System design; Systems analysis; Telecommunication